Comparative analysis of three experimental methods for revealing human fecal microbial diversity - Caiqing Yao; Yu Zhang; Lijun You; Jingjing E; Junguo Wang (BMC Microbiology)
Abstract Due to the heterogeneity of the human gut environment, the gut microbiota is complex and diverse, and has been insufficiently explored. In this study, one fresh fecal sample was cultured using 12 commercial or modified media and incubation of culture plates anaerobically and aerobically, the conventional experienced colony picking (ECP) was first used to isolate the colonies and obtain pure culture strains. On this basis, all the colonies grown on the culture plates were collected for culture-enriched metagenomic sequencing (CEMS), and the original sample was also subjected to direct culture-independent metagenomic sequencing (CIMS), the study compared the effects of three methods for analyzing the microbiota contained in the sample. It was found that compared with CEMS, conventional ECP failed to detect a large proportion of strains grown in culture media, resulting in missed detection of culturable microorganisms in the gut. Microbes identified by CEMS and CIMS showed a low degree of overlap (18% of species), whereas species identified by CEMS and CIMS alone accounted for 36.5% and 45.5%, respectively. It suggests that both culture-dependent and culture-independent approaches are essential in revealing gut microbial diversity. Moreover, based on the CEMS results, growth rate index (GRiD) values for various strains on different media were calculated to predict the optimal medium for bacterial growth; this method can be used to design new media for intestinal microbial isolation, promote the recovery of specific microbiota, and obtain new insights into the human microbiome diversity. This is among the first studies on CEMS of the human gut microbiota.